2022
DOI: 10.1080/10717544.2022.2092238
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesized gold nanoparticles from Pseudobulbus Cremastrae seu Pleiones show efficacy against hepatic carcinoma potentially through immunoregulation

Abstract: Nanobiotechnology, the interface between biology and nanotechnology, has recently emerged in full bloom in the medical field due to its minimal side-effects and high efficiency. To broaden the application of nanobiotechnology, we composed gold nanoparticles from the extract of Pseudobulbus Cremastrae seu Pleiones (PCSP) using an efficient and green procedure. The biosynthesized Au nanoparticles containing PCSP (PCSP-AuNPs) were characterized by UV-vis spectroscopic, transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Therefore, PSP-AuNPs demonstrated greater hepatic carcinoma tumor inhibition effect through immunoregulation than PSP did. In contrast to previous studies, , we synthesized PSP-AuNPs from PSP with high a purity (>90%), and this strength facilitated studying the particular immunoregulation and anticancer function of PSP-AuNPs. We not only synthesized the nanoparticles successfully but also confirmed the anticancer effect on hepatic carcinoma of PSP-AuNPs through immunoregulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, PSP-AuNPs demonstrated greater hepatic carcinoma tumor inhibition effect through immunoregulation than PSP did. In contrast to previous studies, , we synthesized PSP-AuNPs from PSP with high a purity (>90%), and this strength facilitated studying the particular immunoregulation and anticancer function of PSP-AuNPs. We not only synthesized the nanoparticles successfully but also confirmed the anticancer effect on hepatic carcinoma of PSP-AuNPs through immunoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…AuNPs possess advantages, including low toxicity, slowing drug degradation, and reducing the dosage and toxicity of drugs used . AuNPs have been widely used in biomedical fields, including clinical chemistry, immunology, microbiology, the diagnosis, and treatment of malignant tumors. , Previous studies have demonstrated that the effects of the combination of AuNPs with extracts and polysaccharides from TCM are superior to the effects of single TCM ingredients in the treatment of liver cancer. , The most common method for synthesizing AuNPs involves the reduction of dissolving gold salt, such as chloroauric acid. Therefore, AuNPs might be synthesized through the reduction of chloroauric acid with PSP (PSP-AuNPs), reducing the toxicity of drugs and extending the duration of drug circulation to achieve more efficient biological functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation